Tribhuvan Vishwovidhyalayako Anusandhan Niti Tatha Karyakram ak Adhyayan - Sharma, Nilam Kumar (Tribhuvan University Journal, 2010)
Not available. Key words: Research Policy; Tribhuvan University; Nepal <!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif]--> Tribhuvan University Journal Vol. XIX, No. 2, 1996 Page: 135-143 Uploaded Date: 31 October, 2010